GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP TERHADAP PENCEGAHAN HIPERTENSI PADA MAHASISWA (STUDI PADA MAHASISWA UNIVERSITAS DIPONEGORO SEMARANG) - Simanjuntak, Agnes Apria; Adi, Mateus Sakundarno; Hestiningsih, Retno; Saraswati, Lintang Dian (Jurnal Kesehatan Masyarakat (Undip), 2021)
The prevalence of hypertension in Indonesia has increased every year. Hypertension does not only affect the elderly but also young people. There is no research yet about description of the knowledge and attitudes related to hypertension prevention among Diponegoro University students The aim of this study was to describe the knowledge and attitudes of students related to hypertension prevention. This type of study is descriptive observational with cross-sectional study design. The sample of this study amounted to 425 respondents obtained using accidental sampling technique. The variables studied were gender, type of study, family history of hypertension, and level of family support.The results showed that majority of the respondents were female (76,5%), the type of study was non-health (50,6%), did not have a family history of hypertension (60%), had a family that supported the prevention of hypertension (50,6%). A total of 51,5% of respondents have a good level of knowledge, 52% of respondents have a good attitude. From the result was concluded that the majority of students already have a good level of knowledge and attitudes related to hypertension prevention. It is necessary to increase student awareness about hypertension, especially related to hypertension prevention.